Correlation of Agile Maturity Model Level With Perceived Project Success In Indonesian Banks - Muhammad Azimul Irsyadi; Herta Napitupulu; Di Hao (Enrichment : Journal of Management, 2021)
Agile Project Management is considered as project management methodology which have important role in the current rapid changes business environment. Agile maturity model hence provide a structured agile implementation guidance to help continuous implementation and improvement of agile. This research is conducted to assess the correlation of agile maturity model with perceived project success in Indonesian Banks. This research is using Partial Lest Square (Structured Equation Modeling). From 5 levels of agile maturity model, this research found that there are positive correlation between agile maturity model and perceived project success in level 2, 4, and 5. In specific this refer to the project planning, sustainable pace and performance management in each respective level. The result of this research is expected to assist the project practitioners to be more efficient in the implementation and the improvement of agile project management quality.